Brief psychotherapy administered by non-specialised health workers to address risky substance use in patients with multidrug-resistant tuberculosis: a feasibility and acceptability study - Calligaro, G.L.; de Wit, Z.; Cirota, J.; Orrell, C.; Myers-Franchi, Bronwyn; Decker, S.; Stein, D.J.; Sorsdahl, K.; Dawson, R. (2021)
Background: Only 55% of multidrug-resistant tuberculosis (MDR-TB) cases worldwide complete treatment, with problem substance use a risk for default and treatment failure. Nevertheless, there is little research on psychotherapeutic interventions for reducing substance use amongst MDR-TB patients, in general, and on their delivery by non-specialist health workers in particular.